Endometrial cytology in the female cat (Felis catus) during diestrus - Sánchez Riquelme, Alfonso (2017)
The purpose of the study was to describe and quantify cytological findings in the cat’s endometrium (Felis catus). Twenty genital tracts were obtained by ovariohysterectomy. To establish the status of the estrous cycle, vaginal cytology was evaluated and ovarian structures were recorded, resulting that all females were in the luteal phase. According to the presence of corpora lutea and follicles, a classification of the luteal phase was proposed: early diestrus: corpora lutea and follicles of 2 mm (n=3), mid-diestrus: corpora lutea without follicles (n= 4), and late diestrus: corpora lutea and follicles 0.5-1 mm (n=13). In the smears of the uterine mucosa, morphological patterns comparable to those described in the canine species were observed, emphasizing that it is possible to verify a decrease in the proportion of normal endometrial epithelial cells and an increase in cellular degeneration towards the final stage of the luteal phase (p<0.05).